The relationship between personality, coping strategies and alcohol use - Feil, J.; Hasking, Penelope (Routledge, 2008)
In an effort to further understand the role of individual differences in alcohol use, recent research has focused on sensitivity to punishment and reward and the relationship which these predispositions have to substance use. Likewise, considerable research interest has been invested in investigating the role of coping strategies in predicting alcohol use. The current study aimed to expand this research by exploring the moderating role of coping in the relationship between sensitivity to both reward and punishment, and drinking behaviour. A total of 161 participants (55 males; 106 females) completed self-report measures assessing sensitivity to reward and punishment, coping strategies and drinking behaviour. Regression analyses revealed that sensitivity to reward, avoidant and emotion-focused coping strategies were positively related to drinking behaviour. Additionally, emotion-focused strategies were found to moderate the relationship between both sensitivity to reward and punishment, and alcohol use, while avoidant strategies moderated the relationship between sensitivity to reward and drinking. These results suggest a relationship between reward sensitivity and coping in determining alcohol use.